The Use Of Educative Game Tools (Ape) Flannel Boards To Improve The Cognitive Abilities Of Children Aged 5-6 Years At The Baiturrahman Tanjung Islamic Kindergarten - Alawiyah, Tuti; Rahayu, Eka Pamuji (Lembaga Penelitian dan Pendidikan Mandala, 2023)
This research aims to improve cognitive abilities in young children, this is motivated by the underdevelopment of children's cognitive abilities in the aspects of counting and understanding the concepts of shape, size, pattern and color. Children are only able to sort numbers but are not yet able to match the numbers with the objects being counted or children are not even able to understand simple shapes such as geometric shapes, distinguish colors and sizes or shapes from one object to another, and are even familiar with the concept of patterns, children are still confused. . So this research aims to improve children's cognitive abilities through flannel board APE. The flannel board is a simple APE where all the numbers and pictures on the board can be disassembled and assembled, making it easier for teachers or children to play with it. The research method in this study is classroom action research by developing the Kemmis and Mc Taggart model. The data analysis technique is qualitative and quantitative data analysis. The class teacher as a collaborator with the researcher carries out activities together from start to finish. The research results cannot be generalized to every problem. The results of this research can contribute ideas to help answer problems. From the research conducted there was a significant increase in initial mathematical abilities in children aged 4-5 years, namely there was an increase from pre-cycle which only reached 16% to 50% and increased again in the second cycle reaching 66% up to the third cycle to 83 .3% and it can be stated that the use of flannel boards can provide a solution to improve the cognitive abilities of children aged 5-6 years at the Baiturrahman Islamic Kindergarten in Tanjung, North Lombok